Exploring relationships among TPACK constructs and ICT achievement among trainee teachers - Khine, Myint Swe; Ali, Nagla; Afari, Ernest (Education and information technologies, 2017)
Teaching in the classroom today can no longer sustain the interest of students and be effective if the process involves traditional approach - teachers as sole provider of content information. In recent years technology has played a significant role in transforming education to more progressive and interactive activities. However the use of technology itself does not produce positive results in quality of learning and students’ achievement. Teachers must be competent in subject knowledge, pedagogical skills and technological know-how. The Technological Pedagogical Content Knowledge or TPACK as a conceptual framework can guide teachers to understand the complex relations between the six components of the model. There has been numerous studies on TPACK in international contexts beyond cultural and language boundaries. This paper examined recent studies on TPACK in various countries and reports findings from a study conducted with student teachers in the UAE.